KAJIAN DESAIN RUANG PERPUSTAKAAN ANAK DI PULAU UNTUNG JAWA - Indra Gunara Rochyat; Putri Anggraeni Widyastuti (Gestalt : Jurnal Desain Komunikasi Visual, 2020)
The Children's Library Room is a public facility built for children of Untung Jawa residents who manages a literature repository that supports education. The collection of arguments was carried out to find the reasons for an interior design work on the island of Untung Jawa carried out. From direct observation it was decided to study the layout of the furniture in the room. Problems design that is not good causes the maximum service to the community. The target audience of this research is for unproductive communities such as junior high, elementary and early childhood education as well as groups of children and young people who are in location. Interior Design Methodologies are offered at the request of users who are the object of research. Research conducted to provide discussion of the layout in the library space and help create peace and comfort in community life through improving service facilities and can improve skills to improve thinking and increase knowledge about the purpose of partnerships can improve.